SAT0371 Characterization of a SjÖgren's Syndrome-Associated Long Non-Coding RNA at 2P25.1. (9th June 2015) - Ice, J.A.; Adrianto, I.; Li, H.; Rasmussen, A.; Wiley, G.B.; Stone, D.U.; Segal, B.M.; Rhodus, N.L.; Radfar, L.; James, J.A.; Montgomery, C.G.; Scofield, R.H.; et al.
Abstract : Background: Sjögren's syndrome (SS) is a common autoimmune disorder characterized by immune-mediated exocrine gland destruction and systemic inflammation contributing to clinical heterogeneity. The complex regulatory mechanisms governing these responses are poorly understood. We previously performed an RNA-sequencing (RNA-seq) study and identified >2, 600 differentially expressed (DE) transcripts associated with SS. Objectives: This study sought to validate, replicate, and functionally characterize one upregulated long non-coding RNA (lncRNA) mapped to chromosome 2p25.1 to better understand its role in SS pathogenesis. Methods: Technical validation and replication of the 2p25.1 lncRNA upregulation was assessed by qPCR. Bioinformatic analysis using GAMMA-seq was used to identify co-expression patterns of this lncRNA with other transcripts. Cellular expression patterns of the 2p25.1 lncRNA were determined by FACS in 9 distinct immune cell subsets in a healthy control followed by RNA isolation and qPCR to assess expression. Statistical comparisons were made using t-tests and Pearson correlations. Results: RNA-seq showed significant upregulation of the 2p25.1 lncRNA when comparing 27 healthy controls and 57 SS patients ( P adj =3.69x10 -5 ; Fold Change=2.4). Technical validation by qPCR confirmed this finding ( P =0.0096), and correlation with RNA-seq results was observed ( r =0.869). Transcript expression in an independent sample set of 36 SS patients and 21 controls confirmed the lncRNA upregulation ( P =0.0183). Co-expression patterns showed T, NK, and dendritic cell activation, development, and proliferation. Expression levels of the 2p25.1 lncRNA were highest in the CD8 + T cells (RU=3.34), followed by CD56int NK cells (RU=2.08), CD56hi NK cells (RU=0.83), and CD4 + T cells (RU=0.81). Expression was not detected in CD141 + and CD1c + CD11c + myeloid DCs, monocytes, B cells, or pDCs. Conclusions: We have identified, technically validated, and independently replicated the upregulation of a novel SS lncRNA at 2p25.1. Furthermore, we have established that this transcript is highly expressed in CD4 + and CD8 + T cells, and NK cells. This study establishes the 2p25.1 lncRNA as the first associated with SS and lays the groundwork for further functional characterization in the pathogenesis of this complex disorder. Disclosure of Interest: None declared